School Challenges and Services Related to Executive Functioning for Fully Included Middle Schoolers With Autism. (June 2023) - Duncan, Amie; Risley, Sydney; Combs, Angela; Lacey, Heather M.; Hamik, Elizabeth; Fershtman, Chaya; Kneeskern, Ellen; Patel, Meera; Crosby, Lori; Hood, Anna M.; Zoromski, Allison K.; Tamm, Leanne
The educational services available for fully included middle schoolers with autism spectrum disorder (ASD) in the general education setting in the United States are not well known. Even less is known about how the executive functioning (EF) deficits of such youth are addressed in the classroom. The current study sought to identify the challenges, including EF, that middle schoolers with ASD face, determine the services that they receive on their Individualized Education Program (IEP), and also explore specific strategies used to build EF skills at school. A convenience data sample was obtained from focus groups with educational personnel ( n = 15), and qualitative analyses of IEPs were conducted in middle schoolers with ASD with EF deficits ( n = 23). Results confirmed that social communication and EF challenges are common. Multiple services and accommodations were identified, although EF challenges were rarely targeted on IEPs. Factors that may facilitate the success of EF strategies in the classroom are discussed.